The President's Authority in Granting Abolition as State Mercy From A Legal and Political Perspective (Case Study of Tom Lembong's Abolition) - Rizky Nanda Rifa'i; Dani Muhtada (Universitas Negeri Semarang, 2026)
This study examines the authority of the President in granting abolition within the framework of the Indonesian rule of law, focusing on the tension between legal certainty and substantive justice. The main issue of this study is the shift in the function of abolition from a normative corrective mechanism to a pragmatic political instrument, as seen in the controversial case of Thomas Trikasih Lembong. The purpose of this study is to analyze the philosophical and juridical basis of abolition and to evaluate how political dynamics influence the decision to grant abolition in 2025. Using a normative legal research method through a legislative, conceptual, and case approach, this study finds that although abolition has a constitutional basis in Article 14 section (2) of the 1945 Constitution of the Republic of Indonesia, its implementation in the Thomas Lembong case functions as